Trap-related injuries in coypus (Myocastor coypus) and raccoons (Procyon lotor)—an approach to improve animal welfare in live trapping - Gethöffer, Friederike; Schöttes, Franziska M.; Reuschel, Maximilian; Wohlsein, Peter; Beineke, Andreas; Siebert, Ursula (Frontiers in Veterinary Science, 2026)
Live trapping is a common method in wildlife research and management, yet it poses inherent risks to animal welfare. This study systematically evaluated injury incidence and severity in coypus (Myocastor coypus) and raccoons (Procyon lotor) captured using three commercially available live trap types: a standard wooden box trap (WBT), a metallic, sheet metal trap (SMT), and a wire grid trap (WGT). A total of 55 coypus and 45 raccoons were examined following a trap confinement duration of a maximum of six hours. Injuries were assessed using standardized necropsy protocols and categorized by anatomical location, severity, and presumed cause. Results showed species-specific injury patterns, with raccoons exhibiting more frequent and severe injuries than coypus. Raccoons primarily sustained skin lesions and dental trauma, consistent with their manipulative, escape-oriented behavior, while coypu injuries were predominantly localized to the snout and incisors. Although not statistically significant, trap design influenced injury profiles: the WBT was associated with severe injuries in raccoons, particularly to the forelimbs and dentition, while the WGT prompted intense escape behaviors without a proportional increase in trauma. The SMT resulted in fewer external injuries but did present species-specific risks, such as claw-abrasion and tail entrapment. Approximately 93% of raccoons and 55% of coypus exhibited external injuries, including 14 severe cases and 5 confirmed fractures. These findings underscore the importance of species-specific trap assessment and design optimization to mitigate animal suffering. Given the limitations of traditional injury scoring systems and behavioral indicators when applied to wild animals, this study highlights the need for integrated, evidence-based welfare assessments in field settings. Future research should prioritize refinement of trapping methods and standardized welfare evaluation frameworks to support ethical and effective wildlife management.